The Effect of Ketapang Leaf Extract (Terminalia catappa) For Soaking Gouramy Fish Eggs (Osphronemus gouramy) on Hatching Rate and Survival Rate - Wildan Rasyid Mukhtar; Sri Hastuti; Dewi Nurhayati (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
The problem that often occurs in the process of hatching gourami fish eggs is the low egg hatching rate due to fungal attacks. One way to overcome this is by soaking eggs with ketapang leaf extract as an ingredient that has an antifungal effect. This research aims to determine the effect of soaking gouramy eggs (Osphronemus gouramy) in ketapang leaf extract at different doses on the hatching rate. The research was conducted using a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment A uses 0 g/L ketapang leaf extract, treatment B 1 g/L, treatment C 2 g/L, treatment D 3 g/L. The parameters observed in this study were: egg hatchability, larval survival, prevalence of fungi in eggs and water quality parameters of egg hatching and larval rearing media (temperature and pH). The results showed that soaking eggs with ketapang leaf extract had a significant effect (P<0.05) on egg hatchability, fungal prevalence and survival rate. The highest hatching rate value was on treatment C at 88.33±2.08%, followed by treatment D at 84.67±4.51%, treatment B at 78.67±5.13%, and treatment A at 73.67±3.51%. The lowest prevalence value of the fungus that attacks the eggs was in treatments C and D is 10.00±3.51% and 10.67±3.61%, followed by treatment B at 15.00±1.00%, and treatment A at 24.67±4.73%. The highest larval survival value was in treatment C with 81.20±0.74%, followed by treatment D at 79.13±1.93%, treatment B at 75.26±5.81%, treatment A 66.97±3.00%. Water quality for temperatures ranges from 23-28 oC and pH ranges from 6.7-7.5.